Evaluation of a short, all oral treatment regimen including bedaquiline, delamanid, linezolid, clofazimine, and pyrazinamide named “Regimen C” for pre-XDR tuberculosis in Niger - Boubacar Soumana, Soumana; Yacouba, Abdourahamane; Abdoul Lawi, Cheikh Aboubacar; Oumar, Ibrahim; Souleymane, Bassirou; Soumana, Alphazazi; Ounoussa, Tapha; Doutchi, Mahamadou; Daou, Mamane; Brah, Souleymane; Adehossi, Eric; Mamadou, Saidou (Frontiers in Tuberculosis, 2026)
BackgroundThe emergence of extensively drug-resistant tuberculosis (XDR-TB) poses a serious challenge to global tuberculosis control, particularly in high-burden countries like Niger. In 2021, a new fully oral, shorter treatment regimen, named regimen C, was adopted nationally.AimThis study aimed to assess its effectiveness under programmatic conditions.MethodsThis was a retrospective, cross-sectional study conducted from April 2021 to December 2024. All patients with pre-XDR and XDR-TB treated in one of the four multidrug-resistant (MDR) TB units in Niger, who received the new standardized regimen and completed their treatment, were included in the study.ResultsA total of 16 patients with pre-XDR-TB were included in the study. Clinical, microbiological, and radiological data were collected. The median age was 30.5 [interquartile range (IQR) 25–39 years], and 62.5% of patients were male. All patients had pulmonary pre-XDR TB. At the end of treatment, a therapeutic success rate of 75.0% was observed. Adverse events occurred in 88.0% of patients, including 2 cases (14.3%) of grade 4 adverse reactions. Undernourished patients tended to have an increased risk of unfavorable treatment outcomes, although this association was not statistically significant (p = 0.18).ConclusionThese findings suggest that the regimen evaluated in this study appears to be effective for the management of pre-XDR tuberculosis in Niger, with a promising treatment success rate.